Analysis of the Influence of Brand Experience on Brand Attachment and Loyalty of Perfume Consumers Using Gender as a Moderator Variable (Pusat Riset dan Inovasi Nasional, 2025)
Toward HMNS fragrances by incorporating brand passion, brand affection, and self-brand connection as mediating variables, and gender as a moderating variable. The research is motivated by the increasing competition within Indonesia’s local fragrance industry and the growing importance of brand experience in shaping emotional attachment and customer loyalty. A quantitative approach was employed using an online survey distributed to HMNS fragrance consumers who had prior brand usage experience. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that brand experience significantly affects all three dimensions of Emotional Brand Attachment (EBA) : brand passion, self-brand connection, dan brand affection. Furthermore, these mediators significantly influence customer loyalty. Gender was also found to moderate the relationship between brand experience and certain EBA dimensions, suggesting differences in emotional processing between male and female consumers. The findings contribute theoretically by enriching the literature on the role of brand experience and emotional brand attachment within the local fragrance context, and practically by offering insights for HMNS to design more emotionally driven and personalized brand experience strategies.